High-Consistency Optical Fiber Fabry–Perot Pressure Sensor Based on Silicon MEMS Technology for High Temperature Environment - Fei Feng; Pinggang Jia; Jiang Qian; Zhengpeng Hu; Guowen An; Li Qin (Micromachines, 2021)
This paper proposes a high-temperature optical fiber Fabry–Perot pressure sensor based on the micro-electro-mechanical system (MEMS). The sensing structure of the sensor is composed of Pyrex glass wafer and silicon wafer manufactured by mass micromachining through anodic bonding process. The separated sensing head and the gold-plated fiber are welded together by a carbon dioxide laser to form a fiber-optic Fabry–Perot high temperature pressure sensor, which uses a four-layer bonding technology to improve the sealing performance of the Fabry–Perot cavity. The test system of high temperature pressure sensor is set up, and the experimental data obtained are calculated and analyzed. The experimental results showed that the maximum linearity of the optical fiber pressure sensor was 1% in the temperature range of 20–400 °C. The pressure sensor exhibited a high linear sensitivity of about 1.38 nm/KPa at room temperature at a range of pressures from approximarely 0-to 1 MPa. The structure of the sensor is characterized by high consistency, which makes the structure more compact and the manufacturing process more controllable.